Behaviour change intervention for smokeless tobacco (ST) cessation delivered through dentists within a dental setting: a feasibility study protocol - Shaista Rasool; Richard Holliday; Zohaib Khan; Fiona Dobbie; Linda Bauld (BDJ Open, 2022)
Abstract Objectives/Aim To adapt a structured behavioural support intervention for smokeless tobacco (ST) cessation and to assess the feasibility and acceptability of delivering the intervention via dentists within dental settings in Pakistan. Material and methods The study will have 3 phases: (1) Adapt a previously developed intervention to make it suitable for delivery in a clinical/dental setting through qualitative interviews with dental patients and dentists; (2) A multi-centre, pilot randomised control trial in two teaching dental hospitals in Pakistan. Participants (dental patients) will be randomly assigned to intervention or control group in a 1:1 allocation ratio to receive either a structured behavioural support intervention involving face to face counselling or self-help material plus usual care. Each participant will be in the study for approximately 6 months and the overall study is expected to run for 12 months; (3) An embedded qualitative process evaluation. All trial participants will be followed up at 3 and 6 months to assess self-reported ST use. Outcome measures will include: rates of eligibility, recruitment and retention, randomisation group cross-over rates, the provision of data on ST use behaviour, fidelity to the intervention and qualitative assessment of acceptability and feasibility. Discussion Despite the high use of ST in Pakistan, users are offered negligible cessation support. The findings of this multi-centre, mixed-method feasibility study will inform the scope for a larger trial on ST cessation delivered through the existing dental health system.